PENCIPTAAN BUKU POP-UP MESATUA BALI BERJUDUL âI LUBDHAKAâ DENGAN TEKNIK PULL TAB SEBAGAI UPAYA PELESTARIAN BUDAYA TRADISIONAL - Pratama, I Gede Yudha; Bahruddin, Muhammad; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2016)
Abstract: Mesatua Bali is a tradition of storytellingÂ  the Parents to Children. However ,Â  currently Mesatua Bali The culture began to shift because influence of foreign culture and It is rare even society theÂ  apply culture of Masatua Bali. Hence this study aims to the creation pop-up books Mesatua Bali titled âI Lubdhakaâ with pull tab techniques as aneffort to preservation the traditional culture. he study was conducted using with qualitative research methods is to conduct interviews, observation , documentation and literature book study to meet the needs of the data used as materials for concepts the creation pop-up books Mesatua Bali. Through the data analysis is done by a few keywords that are capable of supporting a creative strategy in the creation pop-up books Mesatua Bali to achieve the goal target audience. From the data analysis , the author found the concept âSwadharmaâ. Description of concept " Swadharma " That has Clearly (Something ) obligation to do, will provide awareness and interest to the children to have an obligation to maintain and conserve the traditional culture .Keywords:Â  The creation, Pop-up books, Mesatua Bali, Pull Tab, Preservation Traditional cultures, Swadharma.